Study of Natural Cellulose Fiber’s Characters in Holoptelea integrifolia Tree Bark - Bose Balasubramanian; Thangavelan Udayakumar; Vijaya Kumar Vignesh Kumar; Kandhasamy Raja (Journal of Natural Fibers, 2022)
Natural fibers removed from the bark of Holoptelea integrifolia were characterized by chemical testing, FTIR spectroscopy, XRD, thermal analysis, and FESEM and EDAX morphological analysis. The results of chemical analysis show 65.30% cellulose, 1.36 g/cc density, and 14.69% moisture content. The results of XRD studies show 37.42% crystallinity index and 5.48 nm crystallinity size of the tested samples. Thermal studies show that after 235°C, fiber degradation occurs. SEM results prove the existence of cellulose fibrils and accumulation of polysaccharides over the fiber surface. EDAX shows an O/C ratio of 0.5419. The above results prove that Holoptelea integrifolia can be utilized as a promising reinforcement in polymers for making weightless components.